GEOCHRONOLOGICAL CONSTRAINTS ON THE METAMORPHIC EVOLUTION AT RUNDVAGSHETTA, EAST ANTARCTICA - /; イシカワ, マサヒロ; モトヨシ, ヨウイチ; シムラ, トシアキ; ツチヤ, ノリヨシ /; FRASER, Geoffrey L.; WILLIAMS, Ian S.; ISHIKAWA, Masahiro; MOTOYOSHI, Yoichi; SHIMURA, Toshiaki; TSUCHIYA, Noriyoshi; ELLIS, David J. (National Institute of Polar Research, 1995)
P(論文) The highest grade rocks in the Lutzow-Holm Complex of East Antarctica are exposed at Rundvagshetta, where peak pressures and temperatures are estimated to have reached ∿10kbar, >900℃ (Y. MOTOYOSHI et al.; The 13th Symposium on Antarctic Geosciences, Programme and Abstracts, Tokyo, Natl Inst. Polar Res., 62,1993). K. SHIRAISHI et al. (J. Geol., 102,47,1994) report U/Pb SHRIMP zircon analyses from a garnet-biotite gneiss. Late Archaean-early Proterozoic ages from zircon cores were interpreted as detrital sedimentary ages, while rim overgrowths with a mean age of 521±9Ma were regarded as the time of peak metamorphism. Further SHRIMP zircon analyses (this study) lend support to this interpretation, but provide additional information. Zircon separates from two metapelitic rocks (sample numbers R-125 and R-12) have been analysed. Both samples contain a primary metamorphic assemblage of garnet+sillimanite+orthopyroxene with secondary cordierite forming at the expense of garnet. Sample R-12 also shows cordierite+sapphirine+spinel symplectites around sillimanite. All zircon grains were imaged by cathodoluminescence prior to ion probe analysis, revealing the presence of growth zones with distinct chemistry. Zircons from R-125 fall into two groups based on internal structure. Type I zircons contain cores which are often broken or corroded. These cores yield late Archaean-early Proterozoic ages and are best interpreted as sedimentary detrital zircon. Overgrowing these cores is a euhedral zone, characterised by high U contents (>1000ppm) and very low Th/U ratios (<0.03). This generation of overgrowth, of probable metamorphic origin, yields a late-Proterozoic age, and has not been distinguished in previous work. A second generation of metamorphic overgrowth forms around the high U band. This second generation zircon has much higher Th/U (typically between 0.5 and 1.0), U contents between 100 and 250ppm, and is comparable in age to the zircon rims dated by K. SHIRAISHI et al. (J. Geol., 102,47,1994). Many ...